Coupling finite difference method with finite particle method for modeling viscous incompressible flows. (20th May 2019) - Huang, C.; Long, T.; Liu, M.B.
Summary: A hybrid approach to couple finite difference method (FDM) with finite particle method (FPM) (ie, FDM‐FPM) is developed to simulate viscous incompressible flows. FDM is a grid‐based method that is convenient for implementing multiple or adaptive resolutions and is computationally efficient. FPM is an improved smoothed particle hydrodynamics (SPH), which is widely used in modeling fluid flows with free surfaces and complex boundaries. The proposed FDM‐FPM leverages their advantages and is appealing in modeling viscous incompressible flows to balance accuracy and efficiency. In order to exchange the interface information between FDM and FPM for achieving consistency, stability, and convergence, a transition region is created in the particle region to maintain the stability of the interface between two methods. The mass flux algorithm is defined to control the particle creation and deletion. The mass is updated by N‐S equations instead of the interpolation. In order to allow information exchange, an overlapping zone is defined near the interface. The information of overlapping zone is obtained by an FPM‐type interpolation. Taylor‐Green vortices and lid‐driven shear cavity flows are simulated to test the accuracy and the conservation of the FDM‐FPM hybrid approach. The standing waves and flows around NACA airfoils are further simulated to test the ability to deal with free surfaces and complex boundaries. The results show that FDM‐FPM retains not only the high efficiency of FDM with multiple resolutions but also the ability of FPM in modeling free surfaces and complex boundaries. Abstract : A hybrid approach to couple finite difference method (FDM) with finite particle method (FPM) (ie, FDM‐FPM) is developed to simulate viscous incompressible flows. The upper figure shows the computational model and pressure coefficients for the simulations of flows around an airfoil at Re 10 000, whereas the lower figure shows the vorticity field ω(H/g)1/2 and kinetic energy for simulations of standing waves at Re = 50, respectively. The results show that FDM‐FPM leverages the advantages of FDM in high efficiency with multiple resolutions and FPM in modeling free surfaces.